Technologies of Translocality: Vegetables, Meat and Dresses in Arab Muslim Detroit. (11th November 2016) - Kinder, Kimberley
Abstract: The diversification of US suburbs in terms of race, ethnicity and immigration has created invaluable opportunities for scholars to study technologies of translocality‐in‐the‐making. Translocal landscapes are described as spaces of 'here' studded with 'parts of elsewhere' (Allen and Cochrane, 2007 )—but which pieces of the landscape count as meaningfully 'of elsewhere', how do those parts get there, and what range of meanings can they signify? This article is based on qualitative, in‐depth interviews and explores these questions in the context of an Arab Muslim ethnic enclave and retail district in an inner‐ring suburb of Detroit. The findings indicate that 'parts of elsewhere' are more internally pluralized, multifunctional, multidirectional and aesthetically diverse than commonly recognized. The implications of these findings challenge scholars to develop more robust frameworks to explain how translocal geographies are produced, why they matter, and how they can be recognized.